STANDARDIZATION OF SIDDHA HERBO-MINERAL DRUG AS NANO MEDICINE THROUGH FTIR, ICP-OES AND SEM (International Journal of Ayurveda and Pharma Research, 2020)
Nano medicine in Siddha, is a unique concept and great advancement of Siddhar science. It was clearly explained and documented by many Siddhars by their medicine preparatory and testing methods. They have created many medicines with the use of metals and minerals because of its minimal quantity to avail the high potency results. To reverse the toxicity and adverse reactions they want to convert those heavy metals into Nano particles to modify the physical and chemical characters of the elements. By Drug Delivery Systems (DDS) we can control the Pharmaco Kinetics, Pharmaco Dynamics, non- specific toxicity, immunogenicity and makes bio-recognition and efficacy of drugs. This type of DDS is a major lacuna in our system. To overcome this, now we approach our drug as Novel Drug Delivery System (NDDS). Thirumoolar’s hypothesis about Atomic theory has been reinstated as nanotechnology in this decade. Nano science and technology may be new to the world but Indian systems of Medicines have been using this technology to make Parpam, Chendhuram etc. The physico chemical, Phyto chemical analysis, The FTIR and ICP-OES studies of trial drug Rasa Mezhugu strongly suggesting the safety of the drug by proving heavy metals are in below detectable levels. The active principle Rasam is also within 3ppm as per the admissible level for the medicines. With the help of SEM, the trial drug consists of particles with in 1 to 100nm in size. By this we came to know that the drug has been finished perfectly and able to produce good therapeutic values. By approaching in NDDS, the trial drug increase the therapeutic value, bioavailability and act as smart drug.